One‐pot synthesis of a new high vinyl content hybrid silica monolith dedicated to nanoliquid chromatography. Issue 5 (2nd February 2016) - Racha, El‐Debs; Gay, Pauline; Dugas, Vincent; Demesmay, Claire
Abstract : A new vinyltrimethoxysilane‐based hybrid silica monolith was developed and used as a reversed‐phase capillary column. The synthesis of this rich vinyl hybrid macroporous monolith, by cocondensation of vinyltrimethoxysilane with tetramethoxysilane, was investigated using an unconventional (formamide, nitric acid) porogen/catalyst system. A macroporous hybrid silica monolith with 80% in mass of vinyltrimethoxysilane in the feeding silane solution was obtained and compared to a more conventional low vinyl content hybrid monolith with only of 20% vinyltrimethoxysilane. Monoliths were characterized by scanning electron microscopy, 29 Si nuclear magnetic resonance spectroscopy and N2 adsorption–desorption. About 80% of the vinyl precursor was incorporated in the final materials, leading to 15.9 and 61.5% of Si atoms bonded to vinyl groups for 20% vinyltrimethoxysilane and 80% vinyltrimethoxysilane, respectively. The 80% vinyltrimethoxysilane monolith presents a lower surface area than 20% vinyltrimethoxysilane (159 versus 551 m 2 /g), which is nevertheless compensated by a higher vinyl surface density. Chromatographic properties were evaluated in reversed‐phase mode. Plots of ln( k ) versus percentage of organic modifier were used to assess the reversed‐phase mechanism. Its high content of organic groups leads to high retention properties. Column efficiencies of 170 000 plates/m were measured for this 80% vinyltrimethoxysilane hybrid silica monolith. Long capillary monolithic columns (90 cm) were successfully synthesized ( N = 120 000).